Bacterial species colonizing the vagina of healthy women are not associated with race. (June 2017) - Beamer, May A.; Austin, Michele N.; Avolia, Hilary A.; Meyn, Leslie A.; Bunge, Katherine E.; Hillier, Sharon L.
Abstract: The vaginal microbiota of 36 white versus 25 black asymptomatic women were compared using both cultivation-dependent and -independent identification. Significant differences by race were found in colonization and density of bacterial species. However, exclusion of 12 women with bacterial vaginosis by Nugent criteria resulted in no significant differences by race. Highlights: Asymptomatic genital infections impact vaginal microbiome race-related comparison. Studies of the microbiome should exclude women having asymptomatic infections. No differences found in vaginal microbiome of healthy black versus white women.